Avaliação da versatilidade do MCM-41 funcionalizado - Santos, Danilo Oliveira (2012)
In this work the mesoporous material MCM-41 was functionalized with 3-aminopropyltrimetoxysilane (APS) for several purposes such as adsorption of the remazol red dye, immobilization of lanthanide ions (Eu+3, Tb+3 or Gd+3), coordination with the 2,6-pyridinedicarboxylic acid (dpa) and immobilization of the complex [RuCl2(PPh3)2(Meo-bipy)]. The structural and textural properties of the MCM-41 and NH2-MCM-41 were characterized by absorption spectroscopy in the infrared region, thermal analysis, X-ray diffraction and nitrogen adsorption-dessorption. The adsorption capacity of NH2-MCM-41 was studied with Remazol Red dye. The following parameters were studied in the adsorption process: pH, temperature, adsorbent dosage and initial concentration. The desorption process was studied in a NaOH solution which different concentrations. The Freundlich isotherm model was found to be fit with the equilibrium isotherm data. Kinetics of adsorption follows the modified Avrami rate equation. The NH2-MCM-41 adsorbed 99,1 % of the dye in 360 minutes at 25 ºC. Data from X-ray diffractograms of the NH2-MCM-41-Ln(dpa) (Ln = Eu+3, Tb+3 or Gd+3) material indicated that the materials showed a hexagonal structure with a low degree of ordering. The insertion of the lanthanide ions was indicated by the shift of the amine group of APTS in the spectra of NH2-MCM-41-Ln. The coordination of dpa to NH2-MCM-41-Ln (Ln = Eu+3, Tb+3 or Gd+3) materials was evidenced by the shift of the bands of COH and COO-. The elemental analysis indicated the coordination in the ratio 1:3 (metal:dpa). The nitrogen adsorption analysis shows that with changes in MCM-41, the surface area, pore volume and diameter of the material decreased indicating the immobilization of ions lanthanides and dpa within the pores of the mesoporous material. The evaluation of the triplet level of the ligand, from the spectra of the NH2-MCM-41-Gd(dpa)3 shows that their position favors the energy transfer of metal to ligand for NH2-MCM-41-Eu(dpa)3 material, however the NH2-MCM-41-Tb(dpa)3 material this process is complicated due to the triplet level of ligand is below the issuing level of the Tb+3 ion. Data from X-ray diffractograms of NH2-MCM-41-[RuCl(PPh3)2(Meo-bipy)] showed a hexagonal structure with a low degree of ordering. In addition, the adsorption spectra in the infrared region of the immobilized complex have a displacement in the band 1612 cm-1 characteristic of the ruthenium complex. The thermogravimetric analysis showed that the complex immobilized on the functionalized MCM-41 present high thermal stability compared to free complex. The nitrogen adsorption analysis showed that surface area, pore volume and diameter of the NH2-MCM-41-[RuCl(PPh3)2(Meo-bipy)] are smaller than for the NH2-MCM-41, indicating the immobilization the complex within the pores of the NH2-MCM-41. Catalytic tests for reduction of ketones were carried out with the [RuCl2(PPh3)2(Meo-bipy)] complex. For acetophenone and sulcatone, [RuCl2(PPh3)2(Meo-bipy)] proved to be a good catalyst with 90.50 % and 33.95 % conversion, respectively.